Cardiac function and structure in patients with chronic renal failure - Schärer, Karl; Schmidt, Klaus Georg; Soergel, Marianne (Pediatric nephrology, 1999)
The long-term consequences of cardiac alterations in children with chronic renal failure (CRF) and after renal transplantation (TX) are largely unknown. Studies in adults with end-stage renal disease (ESRD) assume that the fate of many pediatric patients is determined by a high cardiovascular morbidity and mortality. This review describes clinical manifestations, pathophysiology, cardiac function and structure, and management of heart disease in children with CRF and post transplant. Echocardiography and Doppler ultrasonography allow differentiation of three functional disturbances: hypercirculation, systolic left ventricular (LV) dysfunction, and diastolic LV dysfunction, in addition to analysis of LV size and myocardial mass. From adult studies LV hypertrophy is recognized as an early prognostic marker of cardiovascular disease. It is present in about half of children with ESRD and after TX. It may regress, at least in part, by control of hypertension, hypervolemia, and anemia. Experimental studies have shown that, independent of these hemodynamic complications, uremia is associated with structural abnormalities of the heart, which were also described in adult patients with ESRD. These lesions consist mainly of hypertrophy of cardiomyocytes, interstitial fibrosis, and vascular changes (rarefied capillaries, thickened arteriolar walls). Cardiac complications in children with CRF and after TX deserve regular clinical and echocardiographic monitoring in order to minimize later cardiovascular morbidity by appropriate treatment.
Gesehen am 20.01.2021